SIPAS (SISTEM INFORMASI PENGELOLAAN DANA MESJID) - chandra ramdhani, eka; Ramdhani, Eka Chandra; Putra, Muhamad Ilham Destama; Asep, Asep; Natalia, Fransisca (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
The mosque as a place of worship for Muslims, is a very important place, not only a place of worship, but also must be a center of activity for the people. For this reason, the management of mosques must be carried out as well as possible, especially from the management of mosque cash funds. The management of these funds must be carried out professionally and transparently, professional here means that all income and expenditure of funds must be properly accounted for, as well as transparent means that the management of funds can be monitored by the people directly, this is important in order to increase the trust of the people. The Nurul Qolbi Mosque, as one of the mosques belonging to the people, needs to be a mosque with professional management, however, the obstacles faced by this mosque are that mosque receipts and expenses are only recorded in a ledger or logbook, there is no documentation that can be legally accounted for . For this reason, it is necessary to make changes to the procedures for managing mosque funds, based on this, this information system is designed to improve the management of mosque cash fund recording, also so that mosque budget management can be more transparent, because with this application, mosque cash funds can be seen and accessible to the general public.